Dynamic Depth Cues: Mengoptimalkan Alur Pemetaan Paralaks Multi-Lapisan dalam RPG Maker MV/MZ - Wisnu Ade Pradana; Ahmad Rizky Rifai; Jarudin; Erwana Ammarulloh Sunarya (bit-Tech, 2025)
Parallax mapping is a visual rendering technique that creates the illusion of three-dimensional (3D) depth in two-dimensional (2D) game environments by shifting background layers relative to camera movement. While widely supported in advanced game engines such as Unity and Godot, its application in RPG Maker MV/MZ—a platform favored by indie developers for its accessibility—has not been adequately explored in existing game development literature. This study addresses that gap by introducing a custom five-layer parallax mapping pipeline optimized for RPG Maker’s PIXI.js-based renderer, which is not natively designed to support complex depth effects.The proposed system introduces performance-conscious features, including grouped texture loading, dynamic layer visibility (adaptive culling), and a logarithmic depth-scaling method that enhances realism without overwhelming system resources. To evaluate its effectiveness, the study adopts a sequential explanatory mixed-methods approach consisting of two phases: quantitative benchmarking across three hardware tiers (low-end, mid-range, and high-end), and qualitative feedback collection from 20 participants comprising both players and developers. Findings reveal that the system consistently achieves over 46 frames per second (FPS) on low-end devices while improving perceived depth and spatial realism by 38%. Additionally, 85% of users expressed a preference for the parallax-enhanced visuals due to increased immersion and aesthetic quality. These results demonstrate that cinematic visual depth is achievable in RPG Maker with proper optimization, offering practical guidance for developers working under technical constraints.